2013
DOI: 10.2337/dc12-2012
|View full text |Cite
|
Sign up to set email alerts
|

Dual Peroxisome Proliferator–Activated Receptor α/δ Agonist GFT505 Improves Hepatic and Peripheral Insulin Sensitivity in Abdominally Obese Subjects

Abstract: OBJECTIVEThe development of new insulin sensitizers is an unmet need for the treatment of type 2 diabetes. We investigated the effect of GFT505, a dual peroxisome proliferator–activated receptor (PPAR)-α/δ agonist, on peripheral and hepatic insulin sensitivity.RESEARCH DESIGN AND METHODSTwenty-two abdominally obese insulin-resistant males (homeostasis model assessment of insulin resistance >3) were randomly assigned in a randomized crossover study to subsequent 8-week treatment periods with GFT505 (80 mg/day) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
164
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 202 publications
(171 citation statements)
references
References 37 publications
3
164
0
4
Order By: Relevance
“…In phase II clinical trials, GFT505 treatment decreases plasma concentrations of ALT, cGT, and ALP, in MetS patients [9]. Considering its ability to improve peripheral insulin sensitivity and lower plasma FFA levels, likely via PPARd activation, in abdominally obese patients, as well as its TG lowering/HDL increasing activity in subjects with combined dyslipidemia, GFT505 is a promising drug candidate for the treatment of diseases linked to IR, such as T2DM and NASH [146,147].…”
Section: Ppara Agonism In Nafld Therapymentioning
confidence: 99%
“…In phase II clinical trials, GFT505 treatment decreases plasma concentrations of ALT, cGT, and ALP, in MetS patients [9]. Considering its ability to improve peripheral insulin sensitivity and lower plasma FFA levels, likely via PPARd activation, in abdominally obese patients, as well as its TG lowering/HDL increasing activity in subjects with combined dyslipidemia, GFT505 is a promising drug candidate for the treatment of diseases linked to IR, such as T2DM and NASH [146,147].…”
Section: Ppara Agonism In Nafld Therapymentioning
confidence: 99%
“…In addition to PPARg agonists, several studies have investigated the role of PPARa activation in NAFLD since it is involved in lipid and glucose metabolism (Auboeuf et al, 1997;Cariou et al, 2013;Fruchart, 2013;Shiri-Sverdlov et al, 2006). Recently, Pawlak et al, using a pharmacological approach, showed that activation of PPARa inhibited hepatic inflammation and the transition from steatosis toward NASH through a direct, anti-inflammatory mechanism independent of its lipid handling properties (Pawlak et al, 2014).…”
Section: Treatment Of Mets and Nafldmentioning
confidence: 99%
“…Examples include peroxisome proliferatoractivated receptor (PPAR) a,g or PPAR a,d dual agonists [26,27]. Potential targets for such a therapy are the SREBP transcription factors.…”
mentioning
confidence: 99%